Socio-demographic Profile and Outcomes of the Admitted AIDS Patients in BPKIHS (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
In world More than 40 million people are living with HIV/AIDS, 2.3 million are under 15 yrs , 14000 new infections each day , 1.7 million human infected with HIV/AIDS, 3.1 million deaths from AIDS , Million new HIV cases (13425) per day. In south East Asia 6.3 million PLWHA in 2005 (Source: WHO, UNAIDS). It was retrospective descriptive study design conducted at B. P. Koirala Institute of Health Sciences (BPKIHS) among the admitted AIDS cases using their case notes during the period of 1-9-2003 to 30-8-2006 using developed Performa. It was found that Majority of the subjects (83.4%) were of age group 20-40 years, Male (89.6%), and from Sunsari district (47.9%). Half of the subjects were improved after treatment and then discharged. As the number of AIDS cases are increasing rapidly in eastern Nepal and BPKIHS is a centre for treatment of AIDS cases, it is essential to conduct awareness activates regarding prevention of disease and advocacy about available facilities of BPKIHS. Key words: AIDS; Socio-demographic profile; BPKIHS DOI: 10.3126/saarctb.v5i2.3070 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(2) 10-14